Contemporary nutrition strategies to optimize performance in distance runners and race walkers - Burke, L. M.; Jeukendrup, A. E.; Jones, A. M.; Mooses, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Distance events in Athletics include cross country, the 10,000 m track race, half marathon and marathon road races, and 20 and 50 km race walking events, over different terrain and environmental conditions. Race times for elite performers span ~26 min to >4 h, with key factors for success being a high aerobic power, the ability to exercise at a large fraction of this power, and high economy of movement. Nutrition-related contributors include body mass and anthropometry, capacity to use fuels, particularly carbohydrate (CHO) to produce ATP economically over the duration of the event, and maintenance of reasonable hydration status in the face of sweat losses induced by exercise intensity and the environment. Race nutrition strategies include CHO-rich eating in the hours/days prior to the event to store glycogen in amounts sufficient for event fuel needs, and in some cases, in-race consumption of CHO and fluid to offset event losses. Beneficial CHO intakes range from small amounts, including mouth rinsing, in the case of shorter events to high rates of intake (75-90 g/h) in the longest races. A personalized and practiced race nutrition plan should balance the benefits of fluid and CHO consumed within practical opportunities, against the time cost and risk of gut discomfort. In hot environments, pre-race hyperhydration or cooling strategies may provide a small but useful offset to the accrued thermal challenge and fluid deficit. Sports foods (drinks, gels etc) may assist in meeting training/race nutrition plans, with caffeine and, perhaps, nitrate being performance supplements with evidence-based uses.